An auristatin‐based antibody‐drug conjugate targeting HER3 enhances the radiation response in pancreatic cancer. Issue 7 (1st April 2019) - Bourillon, Laura; Bourgier, Céline; Gaborit, Nadège; Garambois, Véronique; Llès, Eva; Zampieri, Alexandre; Ogier, Charline; Jarlier, Marta; Radosevic‐Robin, Nina; Orsetti, Béatrice; Delpech, Hélène; Theillet, Charles; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer characterized by poor response to chemotherapy and radiotherapy due to the lack of efficient therapeutic tools and early diagnostic markers. We previously generated the nonligand competing anti‐HER3 antibody 9F7–F11 that binds to pancreatic tumor cells and induces tumor regression in vivo in experimental models. Here, we asked whether coupling 9F7–F11 with a radiosensitizer, such as monomethylauristatin E (MMAE), by using the antibody‐drug conjugate (ADC) technology could improve radiation therapy efficacy in PDAC. We found that the MMAE‐based HER3 antibody‐drug conjugate (HER3‐ADC) was efficiently internalized in tumor cells, increased the fraction of cells arrested in G2/M, which is the most radiosensitive phase of the cell cycle, and promoted programmed cell death of irradiated HER3‐positive pancreatic cancer cells (BxPC3 and HPAC cell lines). HER3‐ADC decreased the clonogenic survival of irradiated cells by increasing DNA double‐strand break formation (based on γH2AX level), and by modulating DNA damage repair. Tumor radiosensitization with HER3‐ADC favored the inhibition of the AKT‐induced survival pathway, together with more efficient caspase 3/PARP‐mediated apoptosis. Incubation with HER3‐ADC before irradiation synergistically reduced the phosphorylation of STAT3, which is involved in chemoradiation resistance. In vivo, the combination of HER3‐ADC with radiation therapy increased the overall survival of mice harboring BxPC3, HPAC cell xenografts or patient‐derived xenografts, and reduced proliferation (KI67‐positive cells). Combining auristatin radiosensitizer delivery via an HER3‐ADC with radiotherapy is a new promising therapeutic strategy in PDAC. Abstract : What's new? In pancreatic ductal adenocarcinoma (PDAC), chemoradiation is prescribed to patients with borderline resectable lesions to make surgery possible. The HER3 receptor is a key signaling hub in PDAC. Here, the authors developed a novel antibody‐drug conjugate targeting HER3 (HER3‐ADC) that enhanced radiosensitivity of PDAC by arresting cells in G2/M. HER3‐ADC increased radiation response in mice xenografted with PDAC cells, through inhibition of cell survival and induction of DNA break formation and apoptosis. Combining auristatin radiosensitizer delivery via an HER3‐ADC with radiotherapy could help increase the rate of resection for patients with borderline resectable pancreatic cancer.